2014
DOI: 10.1002/phy2.232
|View full text |Cite
|
Sign up to set email alerts
|

Balance control and anti-gravity muscle activity during the experience of fear at heights

Abstract: Fear of heights occurs when a visual stimulus causes the apprehension of losing balance and falling. A moderate form of visual height intolerance (vHI) affects about one third of the general population and has relevant consequences for the quality of life. A quantitative evaluation of balance mechanisms in persons susceptible to vHI during height exposure is missing. VHI‐related changes in postural control were assessed by center‐of‐pressure displacements and electromyographic recordings of selected leg, arm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…These findings are complemented by results from posturographic studies and gait analyses in PPV patients, for they show a typical abnormal strategy for postural control of stance and gait . The constant co‐contraction of the anti‐gravity muscles during normal stance in PVV patients seems to be an expression of the irrational fear of imbalance, also observed in specific phobias . It seems likely that the increase in primary motor cortex structure and connectivity with prefrontal areas reflects the predominant cognitive control of stance and gait.…”
Section: Discussionmentioning
confidence: 78%
“…These findings are complemented by results from posturographic studies and gait analyses in PPV patients, for they show a typical abnormal strategy for postural control of stance and gait . The constant co‐contraction of the anti‐gravity muscles during normal stance in PVV patients seems to be an expression of the irrational fear of imbalance, also observed in specific phobias . It seems likely that the increase in primary motor cortex structure and connectivity with prefrontal areas reflects the predominant cognitive control of stance and gait.…”
Section: Discussionmentioning
confidence: 78%
“…Visual information about body sway becomes less pronounced with increasing distance to the visual surround [5], until visual feedback completely vanishes at a distance of about 20 meters. A recent study of balance control and antigravity muscle activity during the experience of fear of heights showed that alterations in postural sway diminished if there were nearby stationary contrasts in the visual surroundings (looking down with head flexed), or if subjects stood with eyes closed [30]. A recent study of balance control and antigravity muscle activity during the experience of fear of heights showed that alterations in postural sway diminished if there were nearby stationary contrasts in the visual surroundings (looking down with head flexed), or if subjects stood with eyes closed [30].…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is based on earlier findings that postural imbalance at heights originates from a mismatch between the perception of self-motion relative to the surrounding environment when the distance between the nearest visible objects and the eyes reaches a critical threshold (Brandt et al, 1980 ; Salassa and Zapala, 2009 ). Accordingly, both, subjects unsusceptible to vHI (Bles et al, 1980 ) and subjects susceptible to vHI (Wuehr et al, 2014 ) presented an improved postural stabilization under height exposure when nearby stationary contrasts were present in their visual field. The distance to the surrounding at heights is dependent on the head position and the direction of the gaze in space.…”
Section: Introductionmentioning
confidence: 99%
“…Compensation strategies might be represented in the findings of Kugler et al; they reported subjects susceptible to vHI having a reduced visual exploration behavior and a frozen gaze in the straight ahead direction with intermittent fast eye movements toward the ground while walking on a high balcony (Kugler et al, 2014 ). In addition to an impaired visual exploration, an anxiety-driven motor program is thought to be triggered by the height stimulus that intensifies attention on body sway and muscle co-contraction, a process that may contribute to the impaired postural control (Brandt and Huppert, 2014 ; Wuehr et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%